The Impact of Innovative Marketing on the Organization's Reputation by Mediating the Brand _ Field Research in the Oil Marketing Company (SOMO) - Jawad, Aya Shaheen; Jatheer, Saadoun Hammoud (Journal of Economics and Administrative Sciences, 2021)
The research aims to verify that there is an influence between innovative marketing and the organization's reputation by brand mediation.The research problem is that the Oil Marketing Company (SOMO) needs innovative, unconventional methods in marketing its products and improving its reputation by adopting a solid brand that adds value to the product.The importance of the research: The importance of the research is highlighted as it deals with essential variables in business organizations that help increase customer loyalty by adopting a distinctive brand.The research started from four main hypotheses to explore correlations and influence between research variables.The answers of the research sample, which included (221) male and female employees of the Oil Marketing Company (SOMO), were analyzed.Data and information were collected using the questionnaire, personal interviews, as well as the field presence of the researcher, and the data were analyzed using the statistical program (SPSS v.24, AMOS v.23) and a set of statistical methods such as factor analysis, the arithmetic mean, and the standard deviation, Coefficient of variation, correlation coefficient (person), simple linear regression equation, and Soble's test.The study sample members agreed in their answers with a good evaluation level about the innovation marketing variable, especially product innovation and pricing innovation, which explains this result that the SOMO oil company management seeks to adopt multiple marketing methods to increase its oil sales at the local and global levels